2007
DOI: 10.1016/j.virol.2007.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the human immunodeficiency virus type 1-infected monocyte-derived macrophage secretome

Abstract: Mononuclear phagocytes (bone marrow monocyte-derived macrophages, alveolar macrophages, perivascular macrophages, and microglia) are reservoirs and vehicles of dissemination for the human immunodeficiency virus type-1 (HIV-1). How virus alters mononuclear phagocyte immunoregulatory activities to complete its life cycle and influence disease is incompletely understood. In attempts to better understanding the influence of virus on macrophage functions, we used one-dimensional electrophoresis, and liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 52 publications
4
84
0
Order By: Relevance
“…The identified cytoskeletal proteins, including actin and profilin 1, which met the selection criteria are shown in Table I. Other proteins identified were reported elsewhere (22). In agreement with the SELDI-TOF results, profilin 1 and actin were identified.…”
Section: Cytoskeletal Proteinssupporting
confidence: 77%
“…The identified cytoskeletal proteins, including actin and profilin 1, which met the selection criteria are shown in Table I. Other proteins identified were reported elsewhere (22). In agreement with the SELDI-TOF results, profilin 1 and actin were identified.…”
Section: Cytoskeletal Proteinssupporting
confidence: 77%
“…A similar distribution was observed with the percentage of isotope groups (S1 ϭ 17,190; S2 ϭ 17,513) with intensity CVs of Ͻ 50% (81.1% and 90.2% for CSF procurements S1 and S2, respectively). These results are similar to that previously reported for label-free quantitative proteomics measurements (33,38,39). As a measure of peptide preparation reproducibility, equivalent amounts of an internal standard protein, BSA was added to each sample prior to endoprotease digestion.…”
Section: Knowledge-based Analysis Of Proteins Identified In Csfsupporting
confidence: 87%
“…Interestingly, we recently showed that cystatin B expression is increased in HIV-1-infected MDM secretome. 48 Nevertheless, we have not identified this protein in any of 12 CSF samples we examined, making its link to clinical disease unknown at the present time.…”
Section: -D Dige With Saturated Csf Labeling From Had and Nd Hiv-infmentioning
confidence: 80%